The running grave - Galbraith, Robert (Galbraith, Robert. Cormoran Strike novel, 2023)
"In the seventh installment in the Strike series, Cormoran and Robin must rescue a man ensnared in the trap of a dangerous cult. Private Detective Cormoran Strike is contacted by a worried father whose son, Will, has gone to join a religious cult in the depths of the Norfolk countryside. The Universal Humanitarian Church is, on the surface, a peaceable organization that campaigns for a better world. Yet Strike discovers that beneath the surface there are deeply sinister undertones, and unexplained deaths. In order to try to rescue Will, Strike's business partner, Robin Ellacott, decides to infiltrate the cult, and she travels to Norfolk to live incognito among its members. But in doing so, she is unprepared for the dangers that await her there or for the toll it will take on her..."--